Carbon Tax as a Carbon Emissions Controller - Dwinta Mulyanti; Rofily Putriyandari; Abdul Rohman; Renita Rahmawati (Universitas Tidar, 2025)
One of the causes of the currently unpredictable climate change is the release of greenhouse gases into the atmosphere. Indonesia uses a carbon tax policy as a fiscal tool to control greenhouse gas emissions and improve energy efficiency. The main focus of the research is on the implementation mechanisms, the basis for imposition, and its impact on the energy sector, which is one of the major contributors to national emissions. Research methods use quantitative methods with a descriptive approach to process secondary data collected from emission reports, energy consumption documentation, and government regulations by evaluating tariff structure data, sector coverage, and policy effectiveness 2022-2024 period. It is uncovered by the research finding that the average carbon tax burden is substantial, with a rather uniform distribution, which does not substantially decrease emissions. Several difficulties of the policy effectiveness are coming from technical constraints and weak supervision This study contributes to understanding the role of carbon tax in environmental policy in Indonesia, particularly to improve efficiency and control emissions in the energy generation industry. The research results show that the carbon tax contributes to carbon emission savings that are expected to reduce the effects of global warming in Indonesia. In addition, the conducted study contributes to the literature by providing an overview of the calculation of the role of carbon tax in carbon emission efficiency, whereas previous studies focused only on the potential of carbon tax in qualitative observations.